IoT- save the community project - Deepa, N; Agarwal, Rakshit; Uprety, Rohan; Biswas, Anubhab; Venkat Krishna, A (International Journal of Engineering and Technology, 2018)
IoT offers elaborate structures that combine multiple disperse additives towards their synergetic use. The machine suggested within this paper is an answer to track the environment conditions at a selected location while allowing the facts to be seen everywhere around the globe for the propagation of statistics in absence of any current infrastructure. Importance is given on how sensing and communique applications of IoT be utilized successfully in case of catastrophe control. The hardware of the module used for this motive is calculated and elaborated in a detailed way.